A more promising architecture? Commissioners' perspectives on the reconfiguration of personality disorder services under the Offender Personality Disorder (OPD) pathway. Issue 4 (28th November 2019) - Trebilcock, Julie; Jarrett, Manuela; Weaver, Tim; Campbell, Colin; Forrester, Andrew; Walker, Julian; Moran, Paul
Abstract : Purpose: The purpose of this paper is to explore the views of NHS England (NHSE) and Her Majesty's Prison and Probation Service (HMPPS) commissioners about the Offender Personality Disorder (OPD) pathway. Design/methodology/approach: A thematic analysis of four semi-structured interviews with NHSE and HMPPS commissioners is conducted. Findings: Commissioners offered a cautious but confident assessment of the potential effectiveness of the OPD pathway, drawing particular attention to its potential to enhance the confidence and competency of staff, offer better value for money and provide enhanced progression routes for offenders with personality disorders. Additionally, commissioners identified a number of potential risks for the pathway including wider system flux, funding availability, multi-agency working, offender engagement and the need to evidence effectiveness. Research limitations/implications: The analysis is based on a small number of interviews. However, there are only a limited number of commissioners involved with the OPD pathway. Practical implications: While the stronger focus on progression in the OPD pathway is a welcome departure from a narrow focus on high security Dangerous and Severe Personality Disorder (DSPD) services, the foundations of the OPD pathway ultimately lie with the DSPD programme and similar challenges are likely to follow. The system within which the pathway operates is subject to a great deal of flux and this inevitably poses significant challenges for pathway services, staff and offenders, as well as for those of us charged with its evaluation. Originality/value: There has been limited empirical work with commissioners in the mental health field. The paper offers a unique insight into the perspectives of those responsible for commissioning the OPD pathway.